2022
DOI: 10.1097/rlu.0000000000004149
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Nephrotoxicity After 225Ac-PSMA-617 Radioligand Therapy

Abstract: 177 Lu-PSMA-617 radioligand therapy (RLT) has evolved as a suitable alternative to existing therapeutic options in patients with metastatic castration-resistant prostate cancer. With the emergence of α-emitters such as 225 Ac, the efficacy of PSMA-RLT has further improved. Xerostomia and myelosuppression are common early treatment-emergent adverse events in patients receiving this therapy; however, data on long-term toxicity are relatively scarce. In this report, we describe a 76-year-old man with metastatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…An increased risk of acute nephrotoxicity after application of [ 225 Ac]Ac-SibuDAB as compared to [ 225 Ac]Ac-PSMA-617 was not identified under the given experimental conditions. It has to be critically acknowledged, however, that radionephropathy in patients is commonly observed later than two months after administration of the radioligand [ 9 , 36 ]. Although the manifestations may occur earlier in mice than in humans, delayed radiotoxic effects cannot be excluded based on the data presented in this study.…”
Section: Resultsmentioning
confidence: 99%
“…An increased risk of acute nephrotoxicity after application of [ 225 Ac]Ac-SibuDAB as compared to [ 225 Ac]Ac-PSMA-617 was not identified under the given experimental conditions. It has to be critically acknowledged, however, that radionephropathy in patients is commonly observed later than two months after administration of the radioligand [ 9 , 36 ]. Although the manifestations may occur earlier in mice than in humans, delayed radiotoxic effects cannot be excluded based on the data presented in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Studies to date have indicated a low risk of nephrotoxicity with the use of 177 Lu-PSMA-617 for the therapy of hormone-refractory metastatic prostate cancer [45,46]. Nevertheless, nephrotoxicity and tubulointerstitial nephritis are possible side effects, and renal function should be monitored closely during PSMA therapy [47]. As a possible pathogenetic cause, we found PSMA expression in the epithelial cells of the (proximal) tubule system, which is consistent with previous findings in the literature [48].…”
Section: Discussionmentioning
confidence: 99%
“…The most prevalent adverse effect of 225 Ac-PSMA-617 was dry mouth ( 72 74 , 76 78 ), and when administered in conjunction with 177 Lu-PSMA-617, it may lead to a substantial rise in salivary toxicity. Delayed nephrotoxicity has also been documented following 2 cycles of 225 Ac-PSMA-617 RLT ( 79 ).…”
Section: Radionuclide Label Psma-ligand Used For Therapymentioning
confidence: 99%